Tindakan Hukum Terhadap Anak Sebagai Korban Pelecehan Seksual yang Dilakukan Herry Wirawan - Riza Awaludin Rahmansyah; Nurani Nabillah; Anisa Siti Nurjanah (Jurnal Indonesia Sosial Sains, 2022)
In the 2019-2021 era, sexual harassment continues to increase from year to year. According to KEMENPPA, there were 11,057 cases of violence against minors in 2019, 11,279 cases in 2020 and 12,566 cases until November 2021. Sexual violence was experienced by 45 percent of children, 19 percent of psychological violence, and 18 percent of physical violence. Especially regarding the victims are women and children, after the revelation of a case of sexual harassment by the leadership of a pesantren in Bandung. This study aims to provide legal protection to children as victims, provide psychological health protection for children and prevent sexual violence against children. This study uses a qualitative method. According to research findings, sexual harassment in Islamic boarding schools has become more open, thanks to the courage of students who report incidents of sexual harassment. The Child Protection Law, the Criminal Code, and the Criminal Procedure Code all provide legal protection for children who experience sexual harassment (KUHAP). The role of the state apparatus, especially the police as law enforcement officers who carry out the mission of protecting the community, is very much needed in handling these cases. The role of parents is also very important here, because they must act as a source of calm and encouragement for the child so that the incident does not traumatize the child.